(3EKHGJ GdLhgQ GdaQOs - (3eMeO Hf YHO GdcQje Hf CMeO GdTgQSJGfj,J (B548 (3g` s
(3ChdgG (B:s
(3GdLSe efJgi HGdJLQHI Zdi MO dGjbHd GdhUa s
(3BNQgG (B:s
(3hHGdaWfI ajgG gh OGNd GdYGde aGKHJ hdG OGNd ai GdeQcR JeJ hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3GdKGef hGdYTQhfs
(3GfXQ GdeNWhW Qbe (B292s
(3CdMbgG HBNQ cJGH fgGjI GdEbOGes
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI WgQGf (B(1035 / 28) s
Keywords: (3GdJhMjO hGdedd hGdfMds